The Mitochondrial Response to DNA Damage - Rong, Ziye; Tu, Peipei; Xu, Peiqi; Sun, Yan; Yu, Fangfang; Tu, Na; Guo, Lixia; Yang, Yanan (Frontiers in Cell and Developmental Biology, 2021)
Mitochondria are double membrane organelles in eukaryotic cells that provide energy by generating ATP through oxidative phosphorylation. They are crucial to many aspects of cellular metabolism. Mitochondria contain their own DNA that encodes for essential proteins for the execution of normal mitochondrial function. Compared with nuclear DNA, the mitochondrial DNA is more prone to be affected by DNA damaging agents, and accumulated DNA damage may cause mitochondrial dysfunction and lead to a variety of human diseases under certain pathophysiological contexts, including neurodegenerative disorders and cancer. Similar to that in the nucleus, DNA repair machinery within the mitochondria is responsible for repairing DNA damages to maintain the mitochondrial DNA integrity, but how it works remains incompletely understood. In this review, we focus on the current understanding of the mitochondrial DNA repair system. We also discuss other events in the mitochondria that are promoted by excessive DNA damages and inefficient DNA repair, such as mitochondrial fusion, fission, and mitophagy.